The postmodern military armed forces after the Cold War - Moskos, Charles C.; Williams, John Allen 1945-; Segal, David R. (Oxford University Press, 1999)
Assesses contemporary civil-military trends by looking at specific areas in the US military. This book provides the student and defense professional with a foundation on which to base organizational and personal policies. It also tells readers about what life is really like in military, and how it is both the same and different around the world.